LQG/LTR Controller Design for Power Control of Small Pressurized Water Reactors Under Four Feedback-Controlled Strategies. (3rd April 2023) - Wu, Shifa; Wan, Jiashuang; Chen, Zhi; Liao, Longtao; Xiao, Kai; Wang, Pengfei
Abstract: To improve the economy and safety of small pressurized water reactors (SPWRs) with flexible operating characteristics, the reactor power control system should process excellent robustness to provide satisfactory control performances at different operating conditions. This paper proposes four control strategies for reactor power control of SPWRs based on the linear quadratic Gaussian with loop transfer recovery (LQG/LTR) robust control method, including the single-loop reactor power feedback control (RPFC), single-loop average temperature feedback control, dual-loop feedback control, and modified dual-loop feedback control (MDFC) strategies. The corresponding LQG/LTR controllers in the reactor power control system of a SPWR were designed to assess the performance of the four control strategies. The simulation results show that the LQG/LTR controller with the MDFC strategy can provide good control performances for both reactor power and average coolant temperature among the four control strategies while the controller-based single-loop feedback control shows poor control of the reactor power or average coolant temperature. Meanwhile, compared with the existing conventional reactor power control system, the designed robust control system employing the MDFC strategy can provide better control performance for the reactor power and average coolant temperature in full-power operation of 100% to 90% rated power and low-power operation of 25% to 35% rated power with the differential control rod worth taken as 4 pcm/step and 24 pcm/step, indicating its effectiveness and superiority.